2017
DOI: 10.1038/srep41840
|View full text |Cite
|
Sign up to set email alerts
|

Generation of PDGFRα+ Cardioblasts from Pluripotent Stem Cells

Abstract: Isolating actively proliferating cardioblasts is the first crucial step for cardiac regeneration through cell implantation. However, the origin and identity of putative cardioblasts are still unclear. Here, we uncover a novel class of cardiac lineage cells, PDGFRα+Flk1− cardioblasts (PCBs), from mouse and human pluripotent stem cells induced using CsAYTE, a combination of the small molecules Cyclosporin A, the rho-associated coiled-coil kinase inhibitor Y27632, the antioxidant Trolox, and the ALK5 inhibitor EW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 36 publications
0
12
1
Order By: Relevance
“…While previous studies have shown that a single dose of trolox induces low cardiac differentiation efficiency in FACS‐sorted mesodermal cells derived from murine and human PSCs (Cho et al, ; Hong et al, ), our results showed much higher cardiac differentiation efficiency following a single dose of trolox. As the differentiation conditions or cell manipulation processes employed in the present study are different from those in previous studies, the difference in the cardiac differentiation efficiency could be related to the methodological difference.…”
Section: Discussioncontrasting
confidence: 81%
“…While previous studies have shown that a single dose of trolox induces low cardiac differentiation efficiency in FACS‐sorted mesodermal cells derived from murine and human PSCs (Cho et al, ; Hong et al, ), our results showed much higher cardiac differentiation efficiency following a single dose of trolox. As the differentiation conditions or cell manipulation processes employed in the present study are different from those in previous studies, the difference in the cardiac differentiation efficiency could be related to the methodological difference.…”
Section: Discussioncontrasting
confidence: 81%
“…Flk1 + MPCs were sorted by AutoMACS Pro Separator (Miltenyi Biotec). For induction of CLCs, sorted Flk1 + MPCs were plated onto the mitomycin C (AG Scientific)-treated confluent OP9 cells at a density of 5-10 × 10 3 cells cm 2 in the medium containing 3 μg/mL of CsA, 10 μmol/L of Y27632, 400 μmol/L of Trolox, and 1 μg/mL of EW7197 (CsAYTE)[11,17]. The medium was refreshed every other day.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, several studies have been conducted to identify a novel marker for cardiac progenitor or cardiac lineage-committed cells (CLCs), which are intermediate-stage cells between mesodermal cells and differentiated CMs with proliferative capacity[7-10]. Our group previously established a novel class of cells from PSCs-platelet-derived growth factor receptor-α (PDGFRα) + CLCs-induced using a combination of four specific modulators: the mitochondrial permeability transition pore inhibitor cyclosporin A (CsA), the ROCK inhibitor Y27632, the antioxidant Trolox, and the activin A receptor type II-like kinase (ALK5) inhibitor EW7197 (collectively referred to here as CsAYTE)[11]. This novel population of actively proliferating cells is cardiac lineage-committed but in a morphologically and functionally immature state compared with differentiated CMs[11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pluripotent stem cells (PSCs), including embryonic stem cells and induced pluripotent stem cells, are attractive cellular sources for cardiac stem cell therapy [ 5 ]. Various chemical compounds have been studied as potential regulators of the differentiation of PSCs into cardiac lineages, and most of these chemical compounds have been related to diverse signaling pathways involving the bone morphogenetic protein, transforming growth factor, activin, nodal, Wnt, rho-associated coiled-coil kinase, and fibroblast growth factor [ 5 , 6 ]. However, cardiogenic molecules extracted from natural sources remain to be investigated.…”
Section: Introductionmentioning
confidence: 99%